A Hybrid Model for Accurate Energy Analysis of WSN Nodes. (24th January 2011) - Alam Alam, Muhammad Mahtab Muhammad Mahtab; Berder Berder, Olivier Olivier; Menard Menard, Daniel Daniel; Anger Anger, Thomas Thomas; Sentieys Sentieys, Olivier Olivier
Abstract : Energy modeling is an important issue for designing and dimensioning low power wireless sensor networks (WSN). In order to help the developers to optimize the energy spent by WSN nodes, a pragmatic and precise hybrid energy model is proposed. This model considers different scenarios that occur during the communication and evaluates their energy consumption based on software profiling as well as the hardware components power profiles. The proposed model is a combination of analytical derivations and real-time measurements. Firstly, the analytical model provides a global view of various elements of the link and MAC layers and shows their impact on the energy consumption. Secondly, the real-time measurements provide an accurate estimate of the power consumption of the software as well as the hardware platform. These experiments are particularly useful to understand the MAC layer mechanisms, such as wake-up or data collisions for the preamble sampling category, and the energy wasted by collisions is evaluated. The presented model is validated under a specific setup with three different test cases. The results verify that the relative error is between 1 and 8%.